PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP EKSPRESI BRAIN DERIVED NEUROTROPHIC FACTOR DI CREBELLUM RATTUS NORVEGICUS BARU LAHIR - Pitria Permatasari (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
ndonesia's Human Development Index (HDI) for 2015 was ranked 113 out of 188 countries. Education would be needed to raise HDI’s rank. One principle component of education is the quality of the brain. BDNF expression in the brain was affected by many stimuli. Mozart classical music had a neurobiological effect which had ability to increase BDNF. Whereas, other classical musics such as Beethoven and Chopin had never been studied. This study aims to cerebellum’s BDNF expression in the offspring of Rattus norvegicus that ere exposed to the Mozart , Beethoven, Chopin during pregnancy. The method used is pure laboratory experiment with posttest only control group design. The variables measured were BDNF expression in the brain. The samples were divided into 4 groups of each 6 rats. The results showed that significant differences in BDNF expressions between control group and Mozart (p=0,023; p<0,05), between Mozart group and Chopin (p=0,003). There were no statistically detected differences between control group and Beethoven (p=0,256), control group and Chopin (p=0,684), Mozart group and Beethoven (p=0,092) and Beethoven group and Chopin (p=0,292). Based on the above results it can be concluded that the exposure of Mozart’s music during pregnancy had a higher expression of BDNF in the offspring-rat’s cerebellum compare to those which exposed by Beethoven and Chopin’s music.